EFFECT OF ANTIHYPERTENSIVE THERAPY WITH RILMENIDINE ON COGNITIVE FUNCTION IN ELDERLY HYPERTENSIVE PATIENTS - S. V. Nedogoda; U. A. Brel; T. A. Tchalyaby; E. S. Kesareva; V. A. Tcoma (Столичная издательская компания, 2016)
Aim.  To assess antihypertensive efficacy of rilmenidine (Albarel, EGIS, Hungary) and its effect on cognitive function in elderly hypertensive patients. Material and methods. 30 elderly (in average 68 y.o.) hypertensive patients were observed. Each patient received therapy with rilmenidine 2 mg daily during 6 months. 24 hours monitoring of blood pressure before and after therapy was done in each patient. In order to assess cognitive disorders all patients passed neuropsychological tests, which allowed revealing damages of memory, attention, concentration, mental efficiency and psychomotor functions. Raten tests, Veksler test, vocal activity, memory (10 words), serial counting and kinetic probes were used. Results. After 24 weeks of monotherapy with rilmenidine, decrease in daily average systolic blood pressure (SBP) by 7.2% (p<0.01) and diastolic blood pressure (DBP) by 5.5% (p<0.05) was observed. Therapy with rilmenidine showed decrease in daily average burden by SBP and by DBP (by 25.3% and 18.8% respectively; p<0.05) and daily average time index of hypertension for SBP and DBP (by 32.5 and 60.6% respectively; p<0.05) According to the results of neuropsychological tests at the end of treatment, average time for Raten test completion decreased by 16.7% (p<0.05), and for Veksler test completion - by 15.6% (p<0.05). At the same time significant increase in vocal activity of patients is noted: number of words at free associations tests, verbs and plants denomination have grown by 5.8%, 5.1% and 6.3% respectively (p<0.05); number of mistakes in these tests decreased respectively by 71.4%, 50% and 33.3% (p<0.05). Positive dynamics in characteristics of memory: number of words at first and last immediate and postponed reproduction increased respectively by 36.4%, 21.6% and 14.1% (p<0.05),  average time of serial counting and average time of memorization decreased respectively by 13.2% and 31.8% (p<0.05). Velocity in both hands increased, which was observed both in tests on grip and fingering, and on reciprocal coordination. Conclusion. Well-defined antihypertensive effect of rilmenidine in elderly AH patients is accompanied by significant improvement of cognitive functions. This greatly expands opportunities of treatment with rilmenidine in this age group.